Vascular lesions of the pediatric orbit: A radiological walkthrough - Colafati, Giovanna Stefania; Piccirilli, Eleonora; Marrazzo, Antonio; Carboni, Alessia; Diociaiuti, Andrea; El Hachem, May; Esposito, Francesco; Zama, Mario; Rollo, Massimo; Gandolfo, Carlo; Tomà, Paolo (Frontiers in Pediatrics, 2022)
Vascular anomalies of the pediatric orbit represent a heterogeneous group that include both vascular tumors and vascular malformations. The disorder may initially be silent and then associated with symptoms and/or function damage, depending on the type of vascular anomaly and its extension. Vascular tumors include benign, locally aggressive (or borderline) and malignant forms while vascular malformations are divided into “simple”, “combined” and syndromic, or “low flow” or “high flow”. Both entities can arise in isolation or as part of syndromes. In this review, we describe the imaging findings of the vascular lesions of the orbit in the pediatric population, which are key to obtain a correct diagnosis and to guide the appropriate treatment in the light of the new genetic and molecular discoveries, and the role of the radiologist in their multidisciplinary management. We will also touch upon the main syndromes associated with orbital vascular abnormalities.